PHYLOGENETIC EFFECTS, THE LOSS OF COMPLEX CHARACTERS, AND THE EVOLUTION OF DEVELOPMENT IN CALYPTRAEID GASTROPODS - Collin, Rachel (Evolution, 2004)
Despite considerable theoretical and empirical work on the population genetic effects of mode of development in benthic marine invertebrates, it is unclear what factors generate and maintain interspecific variation in mode of development and few studies have examined such variation in a phylogenetic context. Here I combine data on mode of development with a molecular phylogeny of 72 calyptraeid species to test the following hypotheses about the evolution of mode of development: (1) Is the loss of feeding larvae irreversible? (2) Is there a phylogenetic effect on the evolution of mode of development? (3) Do embryos of direct-developing species lose the structures necessary for larval feeding and swimming and, if so, is the degree of embryonic modification correlated with the genetic distance between species? The results of these analyses suggest that mode of development evolves rapidly and with little phylogenetic inertia. There are three cases of the possible regain of feeding larvae, in all cases from direct development with nurse eggs. It appears that species with planktotrophic, lecithotrophic, or direct development with nurse eggs all have equal evolutionary potential and retain the possibility of subsequent evolution of a different mode of development. However, species with direct development from large yolky eggs appear to be subject to phylogenetic constraints and may not be able to subsequently evolve a different mode of development. Finally, species that have more recently evolved direct development have less highly modified embryos than older direct-developing species. Since species with nurse eggs generally have fewer embryonic modifications than those from large yolky eggs, this embryological difference may be the underlying cause of the difference in evolutionary potential.